Lifetime measure of dense and sparse topology sensor network in structural health monitoring - Haque M.E.; Hannan M.A.; Hossain M.F.; Islam M.M.; Abedin M.J. (European Alliance for Innovation, 2023)
Monitoring; Sensor nodes; Topology; Building structural; Computational results; Monitoring system; Network lifetime; Sensing region; Sensor network applications; Structural health; Topology construction; Structural health monitoring